Cognitive screening instrument use in primary care: is it changing?. (July 2014) - Ghadiri-Sani, Mona; Larner, Andrew J
Aim : To measure the frequency of cognitive screening instrument (CSI) use in referrals from primary care to a dedicated secondary care cognitive function clinic.Methods : Over a 6-month period (July–December 2013), referral letters for consecutive patients referred from primary care (n = 140) were examined for mention of CSI use.Results : Although the total number of referrals from primary care increased compared with previous cohorts, there was no significant increase in the proportion (31.4%) administered a CSI before referral. However, newer CSIs specifically designed for use in primary care were used more frequently than previously.Conclusion : There is no evidence from this study that national dementia directives are reducing the observed versus expected dementia diagnosis gap.